Development of a methodology for in-situ dynamic testing of ground support - Shirzadegan, Shahin; Nordlund, Erling; Zhang, Ping (Luleå tekniska universitet, Geoteknologi, 2015)
A series of seven large scale dynamic tests were conducted at LKAB Kiruna mine using explosives in the vicinity of cross-cuts to generate dynamic load on the support system. The aim was to develop an in-situ testing method for rock support, i.e., to determine the dynamic load that causes failure to the test wall and/or support system. The methodology used to design Tests 1 to 7 is discussed in this paper and the level of damage to the test wall and support system in each test is described. Comparison of results in different test designs indicated that increasing burden and number of blasthole at the same time, increases the possibilities of obtaining more planar waves and decreases the destructive effect of detonation gases. Godkänd; 2015; 20150513 (shashi)